Dendrochirotida (Echinodermata: Holothuroidea) from the northeastern coast of Brazil - Prata, Jéssica; de Castro Manso, Cynthia Lara; Christoffersen, Martin Lindsey (Zootaxa, 2020)
The study presents a review of the Dendrochirotida species from shallow waters of the northeastern coast of Brazil. A total of 1,268 specimens were analyzed and 24 species were recorded, which were classified into 16 genera of Cucumariidae, Psolidae, Phyllophoridae, and Sclerodactylidae. Detailed descriptions and figures of the taxonomic characters are provided to facilitate species identification. Notes on morphological variation, geographic distribution, and habitat are also provided. We suggest two new species for science, Thyone brasiliana sp. nov. and Havelockia nietae sp. nov., the new combination Parathyone braziliensis (Verrill, 1868) and the first record of Euthyonidiella trita (Sluiter, 1910) for the Brazilian coast. The bathymetric ranges are expanded for Coronatum baiensis, Euthyonidiella trita, Stolus cognatus, and Thyonidium seguroensis.